The relationship of knowledge management capabilities, learning organization and organizational performance in public sector of Dubai government - Tai, Taufiq Gak Whee; Ngah, Rohana; Yap, Ching Seng (2012)
Knowledge management and learning organization are said to be closely-linked and dependent on each other. However, there are very few researches done in focusing on these two areas relationship especially on the public sectors setting.The purpose of this research is to investigate the impact of knowledge management capability which consisted of knowledge infrastructure capability and knowledge process capability on learning organization.The framework provides useful perspective for investigating knowledge management capability towards learning organization in public sectors in Dubai